2004
DOI: 10.1152/jn.01061.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Common Parieto-Frontal Network Is Recruited Under Both Low Visibility and High Perceptual Interference Conditions

Abstract: A fundamental property of visual attention is to select targets from interfering distractors. However, attention can also facilitate the detectability of near-threshold items presented in isolation. The extent to which these two perceptually challenging conditions are resolved by the same neural mechanisms is not well known. In the present event-related fMRI experiment, subjects performed a letter identification task under two perceptually challenging conditions; when the luminance contrast of a target letter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…We hypothesize that this interaction reflects the impact of top-down attentional mechanisms. Specifically, stronger representation of task-relevant information during high-load trials via top-down attention should result in reduced representation of emotional distracter information caused by representational competition (Desimone and Duncan, 1995;Kastner and Ungerleider, 2000;Marois et al, 2004). We believe that the limited temporal resolution of BOLD data results in the contamination of the rapid, automatic amygdala response to emotional stimuli by the slower, attentionally modulated response.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesize that this interaction reflects the impact of top-down attentional mechanisms. Specifically, stronger representation of task-relevant information during high-load trials via top-down attention should result in reduced representation of emotional distracter information caused by representational competition (Desimone and Duncan, 1995;Kastner and Ungerleider, 2000;Marois et al, 2004). We believe that the limited temporal resolution of BOLD data results in the contamination of the rapid, automatic amygdala response to emotional stimuli by the slower, attentionally modulated response.…”
Section: Discussionmentioning
confidence: 97%
“…The control of task-irrelevant distracters on target processing has been consistently associated with the fronto-parietal network (Kastner & Ungerleider, 2000;Marois et al, 2004;Moran & Desimone, 1985) as well as the ACC (Botvinick et al, 2004;Cohen et al, 2000;Kastner & Ungerleider, 2000;Marois et al, 2000;). Previous studies investigating the response to emotional distraction have also identified the recruitment of frontal, parietal and cingulate cortex (Bishop et al, 2004;Blair et al, 2007;Etkin et al, 2006;Mitchell et al 2007;Vuilleumier, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that such top-down control is mediated by prefrontal-parietal attention network (Hopfinger et al, 2000;Kastner & Ungerleider, 2000;Luck et al, 1997;Marois et al, 2000Marois et al, ,2004Moran & Desimone, 1985;Reynolds et al, 1999) as well as the anterior cingulate cortex (ACC) (Gitelman et al, 1999;Kastner & Ungerleider, 2000;Marois et al, 2000;Posner & Petersen, 1990). But are these attentional areas engaged independent of distracter type?…”
Section: Introductionmentioning
confidence: 99%
“…For example, this interpretation has been the favored account of prefrontal brain areas activated by both observed and performed manual actions and, in this case, has been taken as evidence for a "mirror neuron" system in the human brain (Iacoboni et al, 1999). fMRI studies of phonological retrieval (Price and Friston, 1997), multiple-task performance (Jiang and Kanwisher, 2003), empathy (Singer et al, 2004), and visual attention (Wojciulik and Kanwisher, 1999;Marois et al, 2004) have followed similar logic to make claims about cognitive/ neural mechanisms shared across multiple tasks or stimuli. However, a plausible alternative account of the overlap between hMT, LO, and EBA (and perhaps also for overlapping activations in other brain areas) is that commonly activated voxels contain independent neural systems, each coding for a stimulus or task dimension but intermixed at a resolution below that of individual fMRI voxels.…”
Section: Introductionmentioning
confidence: 99%